Isolation of albumin protein from goatâs milk using anion exchange chromatography - Gaase, Poarasy (2010)
Milk proteins have been extensively studied for over 90 years.The aim of this study was to introduce a simple, reproducible,and less expensive method which is ion exchange chromatography for isolation of albumin protein from goatâs milk.The main whey proteins are Î²-lactoglobuline and Î±- lactalbumin for which genetic variants are also known.The fraction of whey also contains substantial amounts of immunoglobulin and serum albumin.Whey (lactoserum) was obtained by isolating casein from defatted milk using hydrochloric acid.The proteins in the supernatant were fractionated using Q-Sepharose column chromatography for separation.This research were conducted to optimize the pH of the milk sample for separation process.The processes of the separation initialized with sample preparation followed by packing process of ion exchange column,buffer preparation,ion exchange running process and ending by analyzing the ion exchange fraction using reverse process chromatography (PRC).The pH that have been analyzed during this study were milk with pH 5.5, 6.5, 7.5 and 8.5.Result shows that ph 8.5 able to collect Î±-lactalbumin whereas in other pH does not so.Anion exchange chromatography able to isolate BSA and higher concentration was obtained at pH 5.5 with the amount, 0.03616164 mg/ml.RPC method is presented for the determination of albumin method is rapid, reliable and sensitive and gives good accuracy and precision for measurement of the whey proteins.The procedure developed is particularly suited to laboratory-scale applications,but it can also be applied to the purification on a large scale. Separation using simple process and local dairy product which is goat milk able to reduce the cost and time and have potential for commercialization.Standard curve used to analyze the data obtained from RPC analysis.